Pro SQL Server 2005 Database Design and Optimization - Windisch, Kurt.; Kline, Kevin; Davidson, Louis; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2006)
Pro SQL Server 2005 Database Design and Optimization will teach you effective strategies for designing proper databases. It covers everything from how to gather business requirements to logical data modeling and normalization. It then shows you how to implement your design on SQL Server 2005. The authors also describe how to optimize and secure access to this data, covering indexing strategies, SQL design and optimization, and strategies for increased scalability to support large numbers of concurrent users. They provide in-depth advice on optimal code distribution in SQL Server 2005 applications, in the wake of innovations to be able to use .NET code in the database itself. This essential book will ensure that projects have a well-designed database and secure, optimized data access strategies right from the start.
to Database Concepts -- Data Modeling -- Conceptual Data Modeling -- The Normalization Process -- Implementing the Base Table Structures -- Protecting the Integrity of Your Data -- Securing Access to the Data -- Table Structures and Indexing -- Coding for Concurrency -- Code-Level Architectural Decisions -- Database Interoperability.
Keywords: Database management; Software engineering; Database Management; Software Engineering/Programming and Operating Systems